Depression-, Anxiety-, and Anger and Cognitive Functions: Findings From a Longitudinal Prospective Study - Lindert, Jutta; Paul, Kimberley C.; Lachman, Margie E.; Ritz, Beate; Seeman, Teresa E. (Frontiers in Psychiatry, 2021)
Background: Determinants of changes in cognitive function during aging are not well understood. We aimed to estimate the effects of depression-, anxiety- and anger symptoms on cognition and on cognition changes, especially on changes in episodic memory (EM) and executive functioning (EF). Methods: We analyze data from the Mid-Life in the Midlife in the United States Biomarker study at two time points including n=710 women, and n=542 men (1996/1997) at the first assessment and n=669 women, and n=514 men at the second assessment (2013/14). To assess cognition we used the Brief Test of Adult Cognition (BTACT). To measure depression-, anxiety- and anger symptoms we used the Mood and Anxiety Symptom Questionnaire (MASQ), the Center for Epidemiologic Studies Depression Scale (CES-D) and the State-Trait Anger Expression Inventory (STAXI). We used repeated models analyses to explore changes in cognition, and repeated measures linear mixed-effects models to investigate depression, anxiety and anger effects on cognition. Results: At the first assessment, women had significantly better episodic memory functioning than men; men in the oldest age group had significant better executive functioning. At the second assessment, more education, and white ethnicity were associated with less negative changes on episodic memory and executive functioning. Depression- and anger symptoms were associated with declines in episodic memory among women; anxiety symptoms were associated with declines in episodic memory and executive functioning in both gender in men (EF: β: -0.02 (95% CI -0.03, - 0.01; EM: β -0.02 (-0.02, 95% CI: -0.03, - 0.01) and in women (EF: β -0.01, 95% CI: -0.02, - 0.0004; EM: β -0.013, 95% CI: -0.03, -0.001). Conclusions: Depression-, anxiety- and anger symptoms were associated with changes in episodic memory and executive functioning. Further longitudinal studies are critical in populations in more countries to better understand the impact of depression, anxiety and anger symptoms on cognition changes.